Ground Motion Prediction Equations for Far Field Earthquake Considered by Strike Slip Fault Mechanism - S. W., Ahmad; Azlan, Adnan; Rozaimi, Mohd Noor; Ramli, Nazir; Noor Nabilah, Sarbini; Khairunisa, Muthusamy; Awang, Taib; S. K. Muiz, S. K. Razak (2015)
The ground motion prediction equation (GMPE) was developed using regression analysis. This estimation process needs to use a GMPE which provides peak ground acceleration (PGA) estimates incorporating a number of earthquake magnitude, distance and other seismic parameters. The database consisting of more than 35 PGA dataset from different earthquakes recorded by Seismology Station in Malaysia have been used to develop the relationship for this paper. This study aims to investigate the new relationship attenuation to gain exact peak ground acceleration at the location on site. In the Southern Asia region (Indonesia, Philippine and Malaysia) for example, there is significant hazard from earthquake along the strike slip fault.